0328 Extended mortality follow-up of a cohort of workers exposed to acrylonitrile. (21st August 2017) - Koutros, Stella; Blair, Aaron; Graubard, Barry; Lubin, Jay; Stewart, Patricia; Laura, E; Freeman, Beane; Silverman, Debra T
Abstract : Background/Objectives: We extended the mortality follow-up of a cohort of 25 460 workers employed at eight acrylonitrile-producing or using facilities in the U.S by 21 years. Based on 8124 deaths and 1, 023, 921 person-years of follow-up, we evaluated the relationship between occupational exposure to acrylonitrile and mortality. Methods: Standardised mortality ratios using deaths through December 31, 2012 were calculated. Personnel records, work histories, and monitoring data were used to develop quantitative estimates of exposure to acrylonitrile. Adjusted hazard ratios (HR) were estimated by Cox proportional hazards regression. Results: All-cause mortality and mortality from all cancer was significantly less than expected compared with the general population. Internal analyses by cumulative and average exposure revealed elevated risk of cancer of the lung and bronchus (n=808 deaths) and bladder (n=55 deaths). The HR for lung cancer was significantly elevated in the highest quintile of cumulative exposure (1.40, 95% CI 1.11–1.78, p-trend=0.09) compared to unexposed workers, peaking at ≥20 years since first exposure/hire HR=1.49, 95% CI 1.17–1.91); average exposure was associated with a small non-significant increased risk (HR=1.20, 95% CI 0.95–1.52). Average exposure was associated with a significantly elevated risk of bladder cancer; workers in the top tertile had an HR=2.89, 95% CI 1.35–6.18, p-trend=<0.01 compared to the unexposed, while there was non-significant increase between cumulative exposure and risk (HR=1.37, 95% CI 0.65–2.90). Significant HRs were not observed for other smoking-related outcomes. Conclusions: Extended mortality follow-up of the largest cohort of acrylonitrile exposed workers provides some evidence of a possible association between high exposure to acrylonitrile and lung and bladder cancer.